The guardian of the village of Lapinha da Serra - Sequeira, Alexandre Romariz (Farol, 2021)
Based on an artistic proposition of a relational nature, this article deals with the possible intersections between the act of living and the act of creating. I am interested in analyzing the dissociation between the limits of the “empirical person” and the “artist person”, as well as the understanding of the poetic experience under the aegis of an aesthetics of reflection, which does not exhaust its understanding in a simple formal apprehension but invites those who participate to reveal it from associative relationships with its world references.